NSAID-induced diaphragmatic disease of the colon. (24th May 2013) - Munipalle, P C; Little, M; Garud, T; Henderson, D
Abstract : One of the rare side effects of chronic usage of non-steroidal anti-inflammatory drugs is colopathy, which is characterised by colonic inflammation, ulceration and formation of diaphragms in late stages. We treated a case of colonic diaphragm disease with similar findings in our unit recently. We present the case herewith, followed by a discussion of the management of this interesting rare but benign condition.